1995
DOI: 10.1126/science.7846533
|View full text |Cite
|
Sign up to set email alerts
|

Selfish Behavior of Restriction-Modification Systems

Abstract: Plasmids carrying gene pairs encoding type II DNA restriction endonucleases and their cognate modification enzymes were shown to have increased stability in Escherichia coli. The descendants of cells that had lost these genes appeared unable to modify a sufficient number of recognition sites in their chromosomes to protect them from lethal attack by the remaining restriction enzyme molecules. The capacity of these genes to act as a selfish symbiont is likely to have contributed to the evolution of restriction-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
296
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(313 citation statements)
references
References 12 publications
12
296
2
Order By: Relevance
“…In bacteria, methylation is best studied as part of restriction-modification (R-M) systems that have long been considered as contributing to bacterial immune response against incoming DNA including phages 4 . However, recent research has suggested that R-M systems may be 'selfish' elements that protect themselves against removal, through post-segregational killing of newly born progeny by pre-existing and stable restriction enzyme molecules [5][6][7][8][9][10][11] .…”
mentioning
confidence: 99%
“…In bacteria, methylation is best studied as part of restriction-modification (R-M) systems that have long been considered as contributing to bacterial immune response against incoming DNA including phages 4 . However, recent research has suggested that R-M systems may be 'selfish' elements that protect themselves against removal, through post-segregational killing of newly born progeny by pre-existing and stable restriction enzyme molecules [5][6][7][8][9][10][11] .…”
mentioning
confidence: 99%
“…Unmodified target sequences will elicit restriction and the cell will be killed. Some R-M systems therefore have been considered as 'plasmid addiction systems' (Naito et al, 1995 affect the relative stabilities of the restriction enzyme (R 2 M 2 S 1 ) and the modification component (M 2 S 1 ). If this were so, in the absence of ClpXP the loss of hsd genes, like the loss of type II R-M genes, could lead to 'programmed cell death'.…”
Section: Do Proteases Affect the Introduction Of Type I R-m Genes By mentioning
confidence: 99%
“…A third type of postsegregational killing systems consists of several type II restriction-modification (RM) systems (29,31,48). A type II RM system is typically composed of a gene encoding a DNA endonuclease (restriction enzyme), which cleaves double-stranded DNA at a specific recognition sequence, and a gene encoding a DNA methyltransferase (modification enzyme), which methylates the same recognition sequence to protect DNA from the cleavage.…”
mentioning
confidence: 99%
“…According to a hypothesis known as the cellular defense hypothesis, RM systems can provide a defense against invading foreign DNAs such as phage genomes and plasmids and may have been selected and maintained during evolution due to this benefit. Postsegregational host killing allows a plasmid carrying a type II RM gene complex to resist its elimination from host cells by a competitor genetic element (48). Such RM systems with demonstrated capacity for postsegregational killing include PaeR7I, EcoRI, EcoRV, and SsoII (7,36,48,49).…”
mentioning
confidence: 99%
See 1 more Smart Citation